Giant Left Atrial Myxoma Masquerading as Cough-Syncope Syndrome. (August 2017) - Bowman, Jennifer N.; Treece, Jennifer M.; Bhattad, Pradnya Brijmohan; Bochis, Melania; Bajaj, Kailash
Left atrial myxomas are the most common type of benign primary cardiac tumor. Patients can present with generalized symptoms, such as fatigue, symptoms from obstruction of the myxoma, or even embolization of the myxoma causing distal thrombosis. We describe a case with several-month duration of syncopal episodes that occurred after coughing and with exertion. Computed tomography of the chest showed a 6.1 cm by 4.5 cm mass in the left atrium, later evaluated with an echocardiogram. Cardiothoracic surgery removed the mass, and it was determined to be an atrial myxoma. It is important for an internist to be able to diagnose an atrial myxoma because of the risks associated with embolization and even sudden death as myxoma can block blood supply from atrium to ventricle.